How do you simplify #-2(3d - 1) + 4d#?

1 Answer
May 25, 2018

Answer:

#2(1-d)#

Explanation:

Multiply each term in the parenthesis by #-2#:

#-2(3d-1) = (-2)\cdot 3d + (-2)(-1) = -6d+2#

The expression becomes

#-6d+2+4d#

Now sum similar terms: two terms are said to be similar if their literal part is the same. In our case, #-6d# and #4d# have the same literal part #d#, so we can sum them up:

#-6d+2+4d = -6d+4d+2#

#= (-6+4)d+2 = -2d+2#

Finally, you can observe that you can factor a #2# from both terms:

#-2d+2 = 2(-d+1) = 2(1-d)#